Cellular Evidence of Telocytes as Novel Interstitial Cells within the Magnum of Chicken Oviduct. Issue 1 (January 2017) - Yang, Ping; Zhu, Xudong; Wang, Lingling; Ahmed, Nisar; Huang, Yufei; Chen, Hong; Zhang, Qian; Ullah, Shakeeb; Liu, Tengfei; Guo, Dawei; Brohi, Sarfaraz Ahmed; Chen, Qiusheng
Telocytes are a novel type of interstitial cell that has been identified in many organs of mammals, but there is little information available on these cells in avian species. This study shows the latest findings associated with telocytes in the muscular layer and lamina propria of the magnum of chicken oviduct analyzed by transmission electron microscopy. Telocytes are characterized by telopodes, which are thin and long prolongations, and a small amount of cytoplasm rich with mitochondria. Spindle- or triangular-shaped telocytes were detected at various locations in the magnum. In the muscular layer, telocytes have direct connection with smooth muscle cells. The cell body of telocytes along with their long telopodes mainly exists in the interstitial space between the smooth muscle bundles, whereas large numbers of short telopodes are scattered in between the smooth muscle cells. In the lamina propria, extremely long telopodes are twisting around each other and are usually collagen embedded. Both in the lamina propria and muscular layer, telocytes have a close relationship with other cell types, such as immune cells and blood vessels. Telopodes appear with dichotomous branching alternating between the podom and podomer, forming a 3D network structure with complex homo- and heterocellular junctions. In addition, a distinctive size of the vesicles is visible around the telopodes and may be released from telopodes because of the close relation between the vesicle and telopode. All characteristics of telocytes in the magnum indicate that telocytes may play a potential, but important, role in the pathogenesis of oviduct diseases.